Anticorruption in Transition 3 : Who is Succeeding... and Why? - Anderson, James H.; Gray, Cheryl W. (Washington, DC: World Bank, 2012)
There is no room for complacency, however. Corruption is not falling in all countries or all sectors, and even the most successful reformers still tend to have higher levels of firm-level corruption than in Western Europe. The burden weighs most heavily on the new private firms that are the engine of growth and employment in the region. And even in countries that are showing success, the gains are not irreversible. Leaders need to continue to open their economic and political systems to greater competition, foster transparency and accountability in the public sector, and reduce administrative and regulatory burdens for firms.